Determination of Experimental Parameters during Measurement of 40Ar Content in K-Ar Dilution Method - ZHANG Jia; LIU Han-bin; LI Jun-jie; JIN Gui-shan; HAN Juan; ZHANG Jian-feng; SHI Xiao (Yankuang ceshi, 2021)
BACKGROUND The measurement of 40Ar content in K-Ar dilution method includes sample melting and releasing gas, gas purification and enrichment, mass spectrometry measurement. With the application of a newly designed double vacuum furnace and gas purification system, the experiment process gradually changes from manual operation to automatic program control, but the parameters are unclear. OBJECTIVES To determine the parameters by conditional experiments and establish a complete measurement method of 40Ar content in K-Ar dilution method. METHODS Parameters were determined by releasing and absorbing an air standard in activated carbon cold finger with different times, melting different types of samples with different temperatures of the double vacuum furnace. The method reliability was verified by K-Ar dating for SK01 sanidine standard. RESULTS The optimal heating release time for activated carbon cold finger was 500s, and the adsorption time was 200s. Using these conditions, the gas produced by the melting in the furnace can be completely transferred and released to avoid isotope fractionation. The corresponding melting temperature was used for different types of samples to ensure that the samples were completely melted and outgassed, the melting temperature of the furnace for clay minerals, biotite, and muscovite should be set to 1400℃, and 1500℃ for amphibole, 1550℃ for basic rock, and 1600℃for potassium feldspar. The K-Ar dating of 10 sets of SK01 sanidine standards showed that the results were consistent with 40Ar-39Ar dating ages. CONCLUSIONS The obtained condition parameters meet the accurate measurement of 40Ar content using the K-Ar dilution method.